2022
DOI: 10.1097/ico.0000000000003082
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Conventional 8.0-mm Versus Large 9.0-mm Diameter Deep Anterior Lamellar Keratoplasty for Keratoconus

Abstract: The purpose of the study was to compare the clinical outcomes of large 9.0-mm diameter and conventional 8.0-mm bigbubble deep anterior lamellar keratoplasty (DALK). Methods:In this comparative, retrospective interventional case series, medical records of 124 cases of large 9.0-mm diameter DALK from January 2017 to December 2019 and 133 conventional 8.0-mm DALK from January 2014 to December 2016 performed by a single surgeon for the indication of keratoconus were reviewed. Main outcome measures were best specta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have reported a reduction in post-DALK astigmatism if grafts greater than 8 mm are transplanted, with a final mean absolute value of refractive astigmatism recorded in 9-mm grafts of 3.10 6 1.30 D. [16][17][18]32 The first advantage of large diameter grafts is that proximal suture bites and the subsequent circular scarring process of the graft-host interface are further away from the optical center of the cornea, leading to lower and more regular astigmatism. 16 Second, large diameter grafts have the added advantage of excising any residual peripheral pathological ectatic corneal tissue that remains after smaller, conventional diameter DALK, especially in eyes with initial broad ectasias extending beyond 8 mm diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a reduction in post-DALK astigmatism if grafts greater than 8 mm are transplanted, with a final mean absolute value of refractive astigmatism recorded in 9-mm grafts of 3.10 6 1.30 D. [16][17][18]32 The first advantage of large diameter grafts is that proximal suture bites and the subsequent circular scarring process of the graft-host interface are further away from the optical center of the cornea, leading to lower and more regular astigmatism. 16 Second, large diameter grafts have the added advantage of excising any residual peripheral pathological ectatic corneal tissue that remains after smaller, conventional diameter DALK, especially in eyes with initial broad ectasias extending beyond 8 mm diameter.…”
Section: Discussionmentioning
confidence: 99%
“…20 Therefore, it is possible to safely employ larger DALK grafts, up to 9.0 mm in diameter, instead of conventional 8.0-mm grafts. Our group recently compared the outcomes of a series of 124 large 9.0-mm DALK and 133 conventional 8.0-mm DALK performed for KC and reported that large-diameter DALK provided better visual outcomes and signi cantly lower degrees of topographic astigmatism without an increased risk of immune rejection and graft failure, 14 To date, there are no studies that compare the outcomes of large versus small grafts for the treatment of KC according to the characteristics of the conus in terms of size and location. In the present large case series, the visual and topographic outcomes of eyes with KC undergone DALK were reported in relation to graft diameter employed and topographic localization of the ectasia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that employing large-diameter (9.0 mm) lamellar grafts may provide better functional outcomes compared to conventional sized grafts of 8.0 mm due to the lower postoperative astigmatism. [12][13][14] We hypothesize that the advantage obtained using large-diameter grafts might vary according to the characteristics of the keratoconic cornea, in terms of size and location of the conus. 15 The purpose of this study is to evaluate the impact of topographic localization of corneal ectasia on 1year visual and topographic outcomes of DALK employing large (9.0 mm) versus conventional diameter (8.0 mm) grafts.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective interventional case series comparing 124 cases of large 9.0-mm DALK with 133 cases of conventional 8.0-mm DALK, the 9.0-mm DALK group had a significantly higher percentage of eyes achieving higher Snellen BSCVA levels of 20/20 or better (9.0-mm DALK: 44%, 8.0-mm DALK: 26%, P = 0.01) and 20/25 or better (9.0-mm DALK: 74%, 8.0-mm DALK: 59%, P = 0.03). [ 5 ] In the same comparative study, 9.0-mm DALK resulted in significantly lower degrees of astigmatism. The average postoperative refractive astigmatism in the 9.0 mm DALK group was 1 D lower than in the conventional 8.0-mm DALK group.…”
Section: Optimizing Visual Outcomesmentioning
confidence: 94%
“…[ 4 ] Moreover, because the safety advantages of DALK, such as the elimination of the risk of immune endothelial rejection and lower endothelial cell loss, become fully apparent only several years after the surgery, many surgeons may not find a strong enough motivation to overcome the learning curve required to perform this procedure. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%